Contrasting Susceptibilities to Flavescence Dorée in Vitis vinifera, Rootstocks and Wild Vitis Species - Eveillard, Sandrine; Jollard, Camille; Labroussaa, Fabien; Khalil, Dima; Perrin, Mireille; Desqué, Delphine; Salar, Pascal; Razan, Frédérique; Hévin, Cyril; Bordenave, Louis; Foissac, Xavier; Masson, Jean E.; et al. (Frontiers in Plant Science, 2016)
Flavescence dorée (FD) is a quarantine disease of grapevine, involving interactions between the plants, leafhopper vectors, and FD phytoplasma (FDp). Characterising the susceptibility of vine varieties could limit disease propagation. After extensive surveys in vineyards, we showed that Cabernet Sauvignon is highly susceptible, with a high proportion of symptomatic branches and phytoplasma titers, in contrast to Merlot. Localized insect transmissions and grafting showed that phytoplasma circulate in the whole plant in the Cabernet-Sauvignon cultivar, but in Merlot they are restricted to the transmission point. Insect-mediated transmission under high confinement mimicking natural conditions confirmed these phenotypes and allowed the classification of 28 Vitis accessions into three distinct categories, according to the percentage of infected plants and their phytoplasma titers. Reduced symptoms, low phytoplasma titers, and low percentages of infected plants were found to be associated in the Vitis vinifera cultivars tested. Interestingly, the low susceptibility of Merlot was observed for one of its parents, i.e., Magdeleine Noire des Charentes. Rootstocks and their Vitis parents, although having high percentages of infected plants and intermediate to high phytoplasma titers, shared a symptomless response. This is troubling, because rootstocks can constitute a silent reservoir of contamination in mother plants or when they grow wild nearby vineyards. Altogether, data suggest distribution of genetic traits within the Vitis genus involved in insect-mediated phytoplasma transmission, multiplication, circulation and symptom development.